J Nanomed Nanotechnol 2019
DOI: 10.35248/2157-7439.19.10.530
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Green Synthesized Gold Nanoparticles Using Terminalia arjuna against Acetaminophen Induced Hematological Alterations in Male Wistar Rats

Abstract: Background:The present study aim to investigate on the characterization of green synthesized gold nanoparticles (AuNPs) and to evaluate whether this herbal nanoparticle can increase the efficiency of herb for alteration of hematological indices against acetaminophen induced toxicity in male Wistar rats.Methods: Bark extract of Terminalia arjuna was used for the green synthesis of AuNPs and then characterization of the nanoparticles were done. Then experiment was conducted on 24 healthy male Wistar rats. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 32 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…It has been shown that the phytochemical constituents present in plants can act as reducing and capping agents during the synthesis biogenic metallic NPs, including gold nanoparticles (AuNPs) [ 3 , 4 ]. Several studies have demonstrated the synthesis of biogenic AuNPs using various species of the genus Terminalia, which include T. catappa , T. chebula , T. arjuna and T. bellirica [ 5 , 6 , 7 , 8 ]. While TM has been used to produce biogenic silver nanoparticles [ 3 ], this species has not been used to produce AuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the phytochemical constituents present in plants can act as reducing and capping agents during the synthesis biogenic metallic NPs, including gold nanoparticles (AuNPs) [ 3 , 4 ]. Several studies have demonstrated the synthesis of biogenic AuNPs using various species of the genus Terminalia, which include T. catappa , T. chebula , T. arjuna and T. bellirica [ 5 , 6 , 7 , 8 ]. While TM has been used to produce biogenic silver nanoparticles [ 3 ], this species has not been used to produce AuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…There are many application of AuNPs viz. drug delivery [12], antimicrobial [13], anti-cancer [14], antioxidant and catalytic activities [15], antitumor and anti-inflammatory activity [16], hepatoprotective [17], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Taxonomic identification was done by botanist Dr. Dulal Chandra Das, Associate Professor, Department of Botany, Raja Narendra Lal Khan Women's College (Autonomous). Green synthesis of gold nanoparticles (AuNPs) were derived from aqueous bark extract of Terminalia arjuna and characterized as described by Mitra et al 11 Hundred millilitre of 1mM chloroauric acid (HAuCl 4 ) solution was reduced by heating for 10minutes at 60-70 0 C in 10mL of aqueous bark extract of Terminalia arjuna to yield a ruby red colored dispersion.…”
Section: Green Synthesis and Characterization Of Gold Nanoparticles Umentioning
confidence: 99%